The Influence of Profitability, Liquidity, Solvency and Company Growth on Going Audit Opinion - Dinda Dinda (Financial and Accounting Indonesian Research, 2024)
This study aims to assess empirically the partial effect of Profitability, Liquidity, Solvability, and Growth of the Company on Going Concern Audit Opinion. This research is a type of quantitative research. Withdrawal of research hypotheses using the basis of Agency Theory, supported by previous studies that have variable similarities. Research Samples are 12 Mining Companies listed on the Indonesia Stock Exchange. Research variables include Profitability, Liquidity, Solvability, Company Growth and Going Concern Audit Opinion. The type of data used is secondary data from the collection of financial report documents. Using descriptive statistical techniques and assisted logistic regression SPSS 25.0 for data analysis. In addition, this study uses the feasibility test of the Regression model. The results showed that partially Profitability, Solvability and Company Growth had an effect on Going Concern Audit Opinion. While Leverage partially has a positive effect on Going Concern Audit Opinion. Based on the simultaneous test of KAP Reputation, Profitability, Leverage, Solvability, Leverage and Company Growth have a positive effect on Going Concern Audit Opinion. Determination, Profitability, Solvability and Sub -idiaries Growth is 26.6%. One suggestion that is given is that you need to add another variable that can complement the variable gab. So that it can produce 100% of Going Concern Audit Opinion indicators.